An online Chinese-Australian language and cultural exchange through digital storytelling. Issue 2 (4th May 2018) - Oakley, Grace; Pegrum, Mark; Xiong, Xi Bei; Lim, Cher Ping; Yan, Hanbing
ABSTRACT: In a 2013–2014 Australia–China Council project, middle school students in Australia and China shared digital stories about their everyday lives and local cultures, and traditional tales with a modern twist. This article reports on research that aimed to explore the successes and challenges associated with this digital story exchange between Australia and China as a pedagogical approach to support language learning and intercultural understanding. An interpretivist approach was taken, focusing on the perspectives of the teachers. According to the teachers, the exchange was successful to a degree in supporting students' learning in the areas of language, intercultural understanding and twenty-first-century skills, including digital literacies and technological skills, and helped teachers extend their pedagogical horizons. A number of challenges also arose. Analysis of interview data revealed that both the successes and challenges fell into four interrelated domains, which we have labelled structures, practices, capabilities and technologies. This article offers new insights into the exchange of multimodal digital stories as learning activities in the Australian–Chinese context and provides recommendations to guide educators in these four domains.